ANALISIS RANTAI NILAI USAHA BERAS DI KABUPATEN LOMBOK BARAT - Wanda Rismayani (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2023)
The purpose of this research is: (1) Analyse the Main Activity of the Value Chain of Rice Businesses in West Lombok Regency; (2) Analyse the Supporting Activity of Value Chain of Rice in West Lombok Regency; (3) Analyse the Costs and Income of the Value Chain of Rice Businesses Operational in West Lombok. This research uses a descriptive method as the outcome for this research. This research was performed in Lombok District areas which were selected by purposive sampling method. Narmada District area and Gerung District area are chosen as samples for this analysis. The results of this analysis showed that (1) the attainment of the main value chain activity in the rice business in West Lombok Regency was in an outstanding category. The incoming logistics, operations, outgoing logistics, marketing or sales, and services are the indicators of this activity. (2) The accomplishment of value chain supporting activity in the rice business in West Lombok Regency is in a decent category. The company's infrastructure indicators, human resource management, technology development, purchasing or procurement are the indicators that support this activity. (3) Operational costs incurred in two districts areas are in Rp. 2,558,280,834,/average per year and Rp. 10,659,503, -/production. The total average income for procedures for the two sub-districts is Rp. 303,612,022, - per year and Rp. 1,265,050, - per production.